Analisa Interaksi Pelanggan dengan Konsep Social Network Analysis untuk Mengetahui Persepsi Positif dan Negatif berdasarkan Komentar pada Media Sosial Instagram - Ristantya, Amalia; Okiyani, Vivi; Triyandah, Ellana; Febrianti, Friska; Aninditha, Salshabilla; Kamalliah, Siti (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
Telkomsel is one of the largest cellular telecommunications service providers in Indonesia. This analysis uses the Text Mining method and Social Network Analyst (SNA) method to be effective in determining the perception of complaints and excess customers against Telkomsel providers, so the company can improve quality, resolve customer complaints, and Increase Brand Awareness. Based on the results of the analysis there are perceptions of complaints and excess regarding Telkomsel service and facility providers that need to be improved again.